REVIEW OF THE ARTICLE BY HELMUT KURY KORRUPTION - WIRD GESCHMIERT WIE EH UND JE? - A. Klyomin (Russian Journal of Economics and Law)
Review of the article by Kh. Kuri contains gives an estimation of its points, style and structure of the material presentation, the statistical and sociological data about corruption in Germany and other western countries.